Risk Factors for Musculoskeletal Disorders (MSDS) in Hip Workers at Food Agents - Fitriand, Khaifagita; Waldani, Dina; Lestari, Mona; Fujianti, Poppy (GLOBAL HEALTH SCIENCE GROUP, 2025)
Musculoskeletal Disorders (MSDs) are one of the most common occupational health problems, especially among workers who do heavy physical work, such as porters. This study aims to identify risk factors for MSDs in porters at grocery agents in Prabumulih City, South Sumatra, using a cross-sectional study design. This study involved seven main variables, namely work posture, age, nutritional status, length of service, workload, smoking habits, and exercise habits. The research method used was a quantitative approach with a cross-sectional design, with a sample of 73 respondents selected by simple random sampling. The instruments used in this study included a characteristic questionnaire, Nordic Body Map (NBM), Quick Exposure Checklist (QEC), and Cardiovascular Load (%CVL) measurements. Data analysis was carried out univariately and bivariately using the Chi-Square test. The results showed a significant relationship between work posture (p=0.003), age (p=0.045), nutritional status (p=0.004), length of service (p=0.002), workload (p=0.001), and exercise habits (p=0.014) with MSDs complaints. Meanwhile, smoking habits (p=0.072) did not show a significant relationship with MSDs complaints. Based on these findings, it can be concluded that ergonomic factors and worker characteristics play an important role in the emergence of MSDs complaints.